POP-UP BOX EDUCATIONAL APPLICATION “SI DUMBO” MAKES VOICE IN IMPROVING DENTAL AND ORAL HEALTH BEHAVIOR FOR CHILDREN AGED 6-8 YEARS IN A PANDEMIC PERIOD - Trining Widodorini; Astika Swastirani; Nabilah Kusuma Wardhani; Safira Yusinta Rubiyanti; Naadhira Musfira; Yully Endang Hernani (Caring : Jurnal Pengabdian Masyarakat, 2022)
Limitations in conducting online learning due to the COVID-19 pandemic became the background for researchers to create an online version of a pop-up educational storybook that spoke about dental and oral health information. The target of this research is children aged 6-8 years because it is the right age to train motor skills, observe and discover new things and the parents of these children as companions in the development of knowledge and behaviour in maintaining oral health. Therefore, it is very important to provide dental and oral health education as well as familiarize children with brushing teeth at the right time in the right way and to educate parents so that they can guide children regarding behaviour in maintaining dental and oral health. Objective: To increase literacy interest in children from an early age, combining digital technology with conventional books to increase children's and parents' knowledge about dental and oral health as measured through pre-test and post-test questionnaires. Methods: The research used a pre-experimental research method in the form of a one group pre-test-post-test experiment. The sample is selected by the total technique sampling. The independent variable studied was dental and oral health counseling using the Voiced Dumbo Pop Up Box, while the dependent variable in this study was the knowledge of children and parents about oral health as measured by pre-test and post-test questionnaires. Results: Based on the results of the paired T test as a whole, the p value = 0.035 which stated that there was a difference in the total pre and total scores of the post test. Question accuracy which assesses the percentage of pre-test and post-test of children aged 6-8 shows that 98% of the 30 students have answered the post-test accurately and increased (pre-test 86%). Conclusion: The voice of Dumbo's Pop-up Box counseling media was able to significantly increase the knowledge of dental and oral health in students aged 6-8 years at SDN Sukun 3, Malang City.